2021
DOI: 10.1139/cjb-2021-0031
|View full text |Cite
|
Sign up to set email alerts
|

Freezing impact on cone dehiscence, samara release, and seed germination in Casuarina cunninghamiana (Casuarinaceae)

Abstract: Freezing, as a climatic extreme, can contribute to patterns of plant distribution and this might operate through impacts on mechanisms of seed release. Therefore, the impact of freezing on samara release and seed germination in infructescences (cones) of Casuarina cunninghamiana was assessed. Cones at field moisture content were frozen (22 h) and thawed (2 h) though 0 to 5 cycles. Freezing impaired cone dehiscence and samara release (<1% samaras released with ≥2 freezing cycles) and reduced germination from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
2
1
0
Order By: Relevance
“…This study has confirmed the early work with containergrown C. cunninghamiana that demonstrated its cold sensitive (Riley and Saygı 2021b) and extended this to other Allocasuarina and Casuarina accessions in a field context. Notwithstanding this, the growth performance of the accessions tested in this work show that there is clear merit in accessing sheoaks more widely in Turkey in climate zones, e.g., along the Mediterranean and Aegean coasts, where extreme and/or extend subzero temperatures are unlikely to occur.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…This study has confirmed the early work with containergrown C. cunninghamiana that demonstrated its cold sensitive (Riley and Saygı 2021b) and extended this to other Allocasuarina and Casuarina accessions in a field context. Notwithstanding this, the growth performance of the accessions tested in this work show that there is clear merit in accessing sheoaks more widely in Turkey in climate zones, e.g., along the Mediterranean and Aegean coasts, where extreme and/or extend subzero temperatures are unlikely to occur.…”
Section: Discussionsupporting
confidence: 84%
“…Therefore, the key finding of this study was that some species of sheoak have potential for high growth rates under harsh conditions as in Turkey but are not tolerant of the extreme cold of Central Anatolia. At the study location in Niğde, the soil does not normally freeze in winter, so the death of the shoots of the sheoaks was consistent with the results of Riley and Saygı (2021b) but the recovery of some plants from belowground indicates partial root survival. However, this recovery was weak and unlikely to result in the persistence of these species.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation